Pengembangan Modul Berbasis Kurikulum Merdeka Dalam Pembelajaran Biologi Sekolah Menengah Atas - Asni Junita Zega; Novelina Andriani Zega; Agnes Renostini Harefa; Toroziduhu Waruwu (Journal on Education, 2024)
This research aims to determine the feasibility, practicality and effectiveness of developing independent curriculum-based modules in high school biology learning. This type of research is research and development (R&D) using the ADDIE model. Data collection in the research used a questionnaire with a Likert scale which was used to assess the suitability of the module to experts and students' responses to the practicality of the module, as well as assessing the effectiveness of the module using learning outcome tests. The subjects in this research were material, language and media validators, 6 students in class X MIPA 1 for small group trials and 21 students in class X MIPA 2 for field trials. The results of data analysis show that the independent curriculum-based module in high school biology learning is feasible, practical and effective for use, as is known from the validation results by material, language, media experts and the results of student response questionnaires and student learning outcomes. Accumulated validation by material (content) validity of 98.3% and 91.6%, language validity of 95% and media (design) validity of 93.30% with very valid criteria. The average student response results from small group trials reached 90.83% and field tests reached 90.51% with very practical information, while the average learning outcomes of field trial students reached 85.31% with very effective information.